Manifestations of tuberculous infection in children with a positive result of the test with tuberculosis recombinant allergen - E. P. Shilova; L. V. Poddubnaya; I. M. Stepchenko (Туберкулез и болезни лёгких)
The objective: to study manifestations of tuberculous infection in children with a positive result of the test with TRA and determine the tactics for their follow-up.Subjects and methods. In 217 children with a positive result of the test with tuberculosis recombinant allergen (TRA) followed up in a TB dispensary, the results of clinical and radiological (multispiral computed tomography MSCT) examinations were studied and the response to the test with TRA during monitoring (within 3 years) was evaluated to justify terms of dispensary follow-up.Results. It was found that the test with TRA and MSCT allows diagnosing both latent tuberculous infection and detecting minimal post-tuberculous changes (calcifications). Monitoring was performed in 2 groups: Group 1 (n = 112) included patients with newly detected calcifications in the lungs and chest lymph nodes, Group 2 (n = 105) consisted of patients without detected changes in the lungs and chest lymph nodes. The frequency of hyperergic reactions to the test with TRA recorded in patients of both groups was the same (46.7 ± 4.4 and 48.2 ± 4.7%). Results of the test with TRA in children without radiological changes stabilized two years, and in case of calcifications - in three years of follow-up, which allowed predicting the terms of follow-up for such children as belonging to tuberculosis risk group.